STS General Discussion Group: Summary of ALA Midwinter Meeting, January 10, 1998 - Jill Newby (Issues in Science and Technology Librarianship)
Digital dissertations were the topic of discussion at the STS General Discussion Group, Jan. 10th at the New Orleans Convention Center. The two presenters were Gail McMillan, Director of the Scholarly Communication Project, University Libraries at Virginia Tech and Jeff Moyer, from UMI, University Microfilms, Inc.